Formulation and In-Vitro Penetration Test of Ketoprofen Patch with Addition Aloe vera Powder (Aloe vera L.) Bioenhancer - Andini, Septia; Rustiani, Erni; Lathifah, Umi (Universitas Pakuan, 2024)
Ketoprofen is a non-steroidal anti-inflammatory drug (NSAID) which is generally used to reduce pain and inflammation. The main obstacle in administering drugs via transdermal is the low penetration of drugs through the skin. Aloe vera contains lignin compounds which are thought to be bioenhancer. This research aims to formulate ketoprofen and aloe vera powder in form patch and compare penetration patch with and without the addition of aloe vera powder. Preparation patch 3 formulas were made with different ratios of HPMC E5 and Eudragit E100 polymers F1 (6:2), F2 (8:2), F3 (10:2). Formula 3 is the best formula with a comparison of HPMC E5 and Eudragit E 100 of 10:2. Formula 3 has a thin, dry patch and is easy to remove from the mold. F3 then remade with additions bioenhancer by 5 % and patch without additions bioenhancer. The results of the physical quality test showed that the formula with and without the addition of aloe vera as an enhancer has uniform weight, thickness, pH and folding resistance which meets the requirements for patch preparation. Franz diffusion cell result for patch preparations with the addition of aloe vera showed a better penetration value than without the addition of aloe vera with a cumulative value of 92.5815 μg/cm2 and a total flux of 260.4355 μg/cm2 hour.